PET imaging of microglia by targeting macrophage colony-stimulating factor 1 receptor (CSF1R) - Horti, Andrew G; Naik, Ravi; Foss, Catherine A; Minn, Il; Misheneva, Varia; Du, Yong; Wang, Yuchuan; Mathews, William B; Wu, Yunkou; Hall, Andrew; LaCourse, Catherine; Ahn, Hye-Hyun; et al. (Proceedings of the National Academy of Sciences - PNAS, 2019)
While neuroinflammation is an evolving concept and the cells involved and their functions are being defined, microglia are understood to be a key cellular mediator of brain injury and repair. The ability to measure microglial activity specifically and noninvasively would be a boon to the study of neuroinflammation, which is involved in a wide variety of neuropsychiatric disorders including traumatic brain injury, demyelinating disease, Alzheimer's disease (AD), and Parkinson's disease, among others. We have developed [ C]CPPC [5-cyano- -(4-(4-[ C]methylpiperazin-1-yl)-2-(piperidin-1-yl)phenyl)furan-2-carboxamide], a positron-emitting, high-affinity ligand that is specific for the macrophage colony-stimulating factor 1 receptor (CSF1R), the expression of which is essentially restricted to microglia within brain. [ C]CPPC demonstrates high and specific brain uptake in a murine and nonhuman primate lipopolysaccharide model of neuroinflammation. It also shows specific and elevated uptake in a murine model of AD, experimental allergic encephalomyelitis murine model of demyelination and in postmortem brain tissue of patients with AD. Radiation dosimetry in mice indicated [ C]CPPC to be safe for future human studies. [ C]CPPC can be synthesized in sufficient radiochemical yield, purity, and specific radioactivity and possesses binding specificity in relevant models that indicate potential for human PET imaging of CSF1R and the microglial component of neuroinflammation.